Peran Keterampilan Sosial-Emosional Guru terhadap Regulasi Emosi Siswa Sekolah Inklusi - Putri Rahmawati; Edilburga Wulan Saptandari (Jurnal Ilmu Perilaku, 2020)
Emotion Regulation is important for student social interactions. Inclusive school that facilitate diversity can increase the student conflict. Conflict occurs because of the lack of skill in managing emotion. Therefore, the teacher has a task to support the development of student emotional regulation. The purpose of this study was to empirically examine the role of teacher social-emotional skills on emotional regulation in students at inclusive schools. The participants of this study were 109 students aged 9-13 years from three different inclusive schools at Yogyakarta. The method that used is survey by directly distributing the scale. Student perception about teacher social-emotional skills was measured by Teacher Social and Emotional Practice - Student Perspectives, while emotion regulation is measured with emotion regulation scale. Simple linear regression analysis is used to measure the role of teacher social-emotional skills on emotion regulation. The results showed that student perception about teacher social-emotional skills play a positive role on emotion regulation in students at inclusive schools. The higher student perception about teachers’ social-emotional skill the higher students’ emotion regulation.